123k views
0 votes
Consider the following set of equations:Equation M: y = x + 4Equation P: y = 3x + 6Which of the following is a step that can be used to find the solution to the set of equations? x = 3x + 6x + 4 = 3x + 6x + 6 = 3x + 4x = 3x

User Brein
by
4.8k points

1 Answer

1 vote

Solution

Given

Equation M: y = x + 4

Equation P: y = 3x + 6

Equate y = x + 4 in Equation M to y = 3x + 6 in Equation P

Thus, we have

x + 4 = 3x + 6

The answer is x + 4 = 3x + 6

User Srikanth AD
by
4.5k points